Sejarah Pembaharu Islam di Mesir: Jamaluddin Al-Afghani dan Muhammad Abduh - Irfan, Muhammad; Yunus, Abd Rahim; Susmihara, Susmihara (AHKAM, 2024)
This article discusses two significant figures in the history of Egypt, namely Jamaluddin al-Afghani and Muhammad Abduh. Jamal a-Din al-Afghani and Muhammad ‘Abduh were two influential figures in the development of Islam in Egypt. Their thoughts were not only admired in Egypt but also by the Islamic generation in other countries. This research is a literature study with a historical approach. Research data were obtained from various books and articles. Based on the research results, it can be stated that Jamaludin Al-Afghani is one of the Islamic reformist figures with creative ideas to revive the spirit of the Islamic community. He is known as the initiator of the concept of Pan-Islamism. On the other hand, Muhammad Abduh is a rationalist thinker who had a significant impact on the history of Islamic thought. For Abduh, reason holds a high position in religion because through reason, humans can recognize God and understand what must be implemented.